Evaluation of blue mussels (Mytilus edulis) as substrate for biogas production in Kalmar County (Sweden). (April 2018) - Wollak, Birte; Forss, Jörgen; Welander, Ulrika
Abstract: The Baltic Sea is an over-fertilized inland sea; the blue mussels have potential to absorb nutrients as well as being a source of renewable energy in the form of biogas. The aim of this study was to evaluate technology to utilize blue mussels for biogas production in a pilot scale. Blue mussels ( Mytilus edulis ) were anaerobically digested in a two-stage digestion process (430 L), consisting of a percolation bed and an up-flow anaerobic sludge blanket reactor. Frozen mussels with shells were placed in the percolation bed and digestion was performed at 36  ° C during 37 days. The methane potential achieved with this technique was 310 L kg −1 volatile solid substances (273.15 K, 101.3 kPa). This result suggests that blue mussels can be efficiently digested in a larger scale and have the potential of contributing to a sustainable energy mix in the Baltic region and at the same time decrease the eutrophication of the Baltic Sea. No addition of nutrients and no pretreatment of the mussels (peeling) were needed. Graphical abstract: Highlights: Blue mussels have the potential of being an efficient biogas substrate not needing any farmland. The mussel shells left after the digestion might be an efficient soil improver to decrease acidification. The digestion of blue mussels has the potential to contribute to decreased eutrophication.